PENGARUH TUMPAHAN BAHAN BAKAR MINYAK DAN OLI TERHADAP KINERJA CAMPURAN LATASTON-WC DENGAN MENGGUNAKAN METODE MARSHALL - Pataras, Mirka; Astira, Imron Fikri; Kurniawan, Fuad Hasan (CANTILEVER, 2017)
Road pavement is structural section of traffic lane which has central position in road body. Road pavement age is related to surface durability which can be influenced by oil spill accidently especially for gasoline, diesel oil and lubricant brought by vehicle, so it may decrease road and service age. Because of that, this research will detect the fact of influences by spilling oil out to Lataston-WC. In planning pavement layer model, mix and material testing must be done. There were 15 normal samples in this research with KAR (Pb) to define KAO value and 24 samples with KAO value to be soaked with fuel and lubricant in duration vary from 1, 3 and 5 minutes. Marshall test was done by 1 hour later. Then, it was analyzed and concluded. The result showed that asphalt optimum capacity reached 6,7% which then samples be made and soaked in fuel and lubricant. For normal mix samples, stability value reached 1951,87 kg and soaked samples with 5 minutes duration reached 511,56 kg. It can be concluded that duration of soaking also influences in decreasing stability value.